INTEND, DEPICTION IN VITRO AND IN VIVO APPRAISAL OF GLIPIZIDE FLOATING MICROSPHERES USING ETHYL CELLLULOSE AND HYDROXYL PROPYL METHYL CELLULOSE AS POLYMER BY SUBSTANTIALLY MODIFIED METHOD - Gupta, Rishikesh; Prajapati, Sk; Pattnaik, Snigdha; Bhardwaj, Peeyush (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The purpose of this research was to formulate and evaluate floating microsphere of glipizide. Methods: Glipizide microsphere containing ethyl cellulose (EC) and hydroxyl propyl methyl cellulose (HPMC) were prepared by solvent evaporation method. Polymer to drug ratio affected characteristics of microspheres. Microspheres were discrete, spherical, and perforated form. The microspheres exhibited good floating property and achieved good gastric retention. Result: In vitro performance was evaluated by the usual pharmacopoeial and other tests such as drug polymer compatibility (Fourier transform infrared scan), yield (%), micrometric properties such as tapped density (%). Compressibility particle size analysis (by optical microscopy), drug entrapment efficiency, surface topography (scanning electron microscope), and in vitro release study. On the basis of results, increasing the polymer ratio increased the particle size (195.6±20.24 to 200.89±16.61), increased tapped density (maximum 0.29.60±0.00037 HGF4, batch), and decreased % compressibility (2.13±0.188). Drug loaded floating microspheres were found to be float more than 12 hrs on simulated gastric fluid (pH-1.2). Maximum drug entrapment was found in batch HGF3 (Drug:HPMC:EC) (1:1:3). Electron microscopy showed its perforated surface with hollowness. After 10 hrs, maximum release was found to be 78.0% (batch-GF1). Conclusion: The release study was performed in simulated gastric fluid with 0.02% tween80. The best release result was obtained at the ratio of drug: polymer (1:1). Keywords: Floating microspheres, Glipizide, Gastrorentensive system, In vitro release.